A Phase I Study to Evaluate the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of Recombinant Human Hyaluronidase PH20 Administered Intravenously in Healthy Volunteers - Marie A. Printz, BA; Samuel S. Dychter, MD; Emanuel P. DeNoia, MD; Rena Harrigan, MPH; Barry J. Sugarman, PhD; Monica Zepeda, PhD; Jennifer Souratha, BSc; David W. Kang, BSc; Daniel C. Maneval, PhD (Elsevier, 2020)
ABSTRACT: Background: Recombinant human hyaluronidase PH20 (rHuPH20) is used in subcutaneous formulations (eg, RITUXAN HYCELA [rituximab and hyaluronidase human], HERCEPTIN HYLECTA [trastuzumab and hyaluronidase-oysk], PHESGO [pertuzumab/trastuzumab/hyaluronidase-zzxf], and Darzalex FASPRO [daratumumab and hyaluronidase-fihj]) to increase the dispersion and absorption of coadministered therapeutics. Although unlikely, subcutaneous products that include rHuPH20 could be mistaken for the intravenous formulation of the corresponding drugs (eg, RITUXAN [rituximab], HERCEPTIN [trastuzumab], and DARZALEX [daratumumab]). To understand the potential effects of inadvertent intravenous injection of rHuPH20, we investigated the safety profile, pharmacokinetics (PK), and pharmacodynamics (PD) of rHuPH20 administered intravenously. Objectives: This Phase I, open-label, single-center study in healthy volunteers was designed to assess the safety profile, tolerability, PK, and PD of rHuPH20 administered intravenously. Methods: Healthy volunteers received 5 mL intravenous infusion of either 10,000 U (n = 12) or 30,000 U (n = 12) rHuPH20 over 5 minutes. Blood samples for PK and PD analysis were obtained at baseline and at various times after initiation of infusion. Adverse events and laboratory parameters were measured to assess the safety profile and tolerability of the intravenous infusion. The PK of rHuPH20 was assessed using both an enzymatic assay and a mass-based immunoassay, and plasma hyaluronan concentrations were measured as a PD marker using an HPLC-MS/MS disaccharide assay. Results: All 24 volunteers (mean age = 36.5 years) completed the study, and no serious adverse events were reported in either treatment group. Overall, 2 adverse events (both Grade 1) were reported; catheter site pain in the 10,000 U group and hypotension in the 30,000 U group. Plasma concentrations of rHuPH20 increased during the 5-minute intravenous infusion (median tmax = 6 minutes from intravenous initiation) followed by a rapid plasma clearance (t1/2 ∼10 minutes from intravenous initiation). Plasma hyaluronan concentrations increased with dose and time (tmax range = 45‒120 minutes from intravenous initiation) and returned to baseline within 1 week of administration. Changes in both PK and PD measurements appeared proportional to dose. Conclusions: The study demonstrated that intravenous administration of up to 30,000 U rHuPH20 was well tolerated, rapidly cleared from the plasma, and did not appear to be associated with any serious adverse effects at doses used in subcutaneous therapeutic products. (Curr Ther Res Clin Exp. 2020; 81)